The Impact of the Digital Health Interventions in Curbing COVID-19 in Zimbabwe - Chidhau, Stephen; Mutizwa, Bismark; R. Muzama, Tinashe (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2021)
Amid ongoing research about, Digital Health Interventions (DHI) in Zimbabwe, is the largely overlooked impact of DHI to mitigate the spread of COVID-19. To contribute towards filling this knowledge gap, the study seeks to examine the DHI strategies that have been adopted to curb the inimical effects of COVID-19 in Zimbabwe. DHI such as telemedicine, use of social media, Electronic Medical Records (EMRs), Mobile Health (mHealth), and Healthcare Information Systems (HIS) have been disposed to curtail the spread of COVID-19. The limitations and hurdles crippling DHI are discussed extensively. This study adopts a qualitative research design, comprising personal and targeted interviews and documentary review. Preliminary findings are that DHIs are effectively working for employing routine and innovative forms of Information and Communications Technology (ICT) to address health needs. However, the research noted that various factors such as corruption lack of funding, shortage of qualified workforce and medical expertise, and weak healthcare infrastructure are militating against robust deployment of DHIs. This study includes measures that can be adopted to address these challenges.